(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The profound and objective changes taking place in the modern world have changed ethnic history, culture, values, language, etc. Kyrgyz youth. Forgetting is one of the main problems of our time. Therefore, the mentioned article interprets in detail the concepts of cultural and moral values, heritage and sacred heritage, provides rich information on the ethnoetiquette of the Kyrgyz people, and this plays a key role in understanding the own culture and values of the young men and women of Kyrgyzstan.